The Effect Of Financing To Deposit Ratio, Financing Restructuring And Foreclosed Collateral On The Level Of Problem Financing In Islamic Commercial Banks In Indonesia In The Period 2019-2023 - Pujastuti, Deti; Tripuspitorini, Fifi Afiyanti; Nugraha, Muhamad Arif (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Islamic Commercial Banks have faced complex challenges in recent years, such as the covid-19 pandemic, market dynamics, economic instability, and commodity price fluctuations, which have affected their intermediation function. Non-performing financing (NPF) remains one of the primary risks. This study analyzes the effect of Financing-to-Deposit Ratio (FDR), financing restructuring, and Foreclosed Collateral (AYDA) on the NPF level at Islamic Commercial Banks in Indonesia for the period 2019–2023. Descriptive quantitative methods are used with secondary data from quarterly reports through documentation techniques and literature studies. Panel data regression analysis was applied to a sample of five banks in this study. The results of the study indicate that financing restructuring and foreclosed collateral have a significant effect on non-performing loans, while FDR does not have a significant effect. Simultaneously, FDR, financing restructuring and foreclosed collateral have a significant effect on non-performing financing. This study is expected to contribute to Islamic commercial banks' strategies in managing financing risks in reducing non-performing financing.